1981
DOI: 10.1007/bf00199264
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cells in carcinomatous pleural effusions

Abstract: Summary. Effector cells in carcinomatous pleural

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

1981
1981
1998
1998

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 23 publications
(35 reference statements)
3
22
0
1
Order By: Relevance
“…The response was expressed both as the aggregation angle alpha and as the maximal amplitude. N K cell activity was studied as previously described in detail [34] using the patients' isolated mononuclear bone marrow and peripheral blood cells as effector cell populations, with 51Cr-labeled K562 cells as targets. Briefly, 100 ~tl 51Cr-labeled target cells and 100 lxl effector cells were placed into round-bottomed wells of microtiter plates (Nunc, Rokskilde, Denmark) at effector/target ratios of 40: 1, 20: 1, and 10: 1.…”
Section: Methodsmentioning
confidence: 99%
“…The response was expressed both as the aggregation angle alpha and as the maximal amplitude. N K cell activity was studied as previously described in detail [34] using the patients' isolated mononuclear bone marrow and peripheral blood cells as effector cell populations, with 51Cr-labeled K562 cells as targets. Briefly, 100 ~tl 51Cr-labeled target cells and 100 lxl effector cells were placed into round-bottomed wells of microtiter plates (Nunc, Rokskilde, Denmark) at effector/target ratios of 40: 1, 20: 1, and 10: 1.…”
Section: Methodsmentioning
confidence: 99%
“…The cytotoxicity of malignant pleural effusion lymphocytes (MPEL) against autologous tumor cells was compared with that of peripheral blood lymphocytes (PBL). The cytotoxicity of MPEL was found to be lower than that of PBL [23][24][25]. An evaluation of lymphocytes in nonsmall-cell lung cancer shows a decrease in the percentage of NK cells which has been reduced in TILs as compared to PBLs.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action is, however, a matter of controversy. It has been suggested that induction of IFN is not involved in augmentation of NK activity by this agent (Uchida & Micksche, 1982 Although suppressor mechanisms can be demonstrated in the ascites of some ovarian cancer patients (Allavena et al, 1981;Introna et al, 1982) evidence has suggested that defective NK activity of TAL was mainly related to a low frequency of LGL (Introna et al, 1983;Introna & Mantovani, 1983) unlike pleural effusions where high numbers of LGL were reported (Uchida & Micksche, 1981a). Hence it appears unlikely that interference with suppressor mechanisms plays a major role in boosting of NK activity of TAL from ascites ovarian tumours.…”
Section: Discussionmentioning
confidence: 99%